Prawo i etyka – dwa bieguny publicznej debaty dotyczącej spraw gospodarczych - Rotengruber, Przemysław (Annales. Etyka w Życiu Gospodarczym, 2010)
Business ethics is usually seen as set of communicates addressed to representatives of the sphere of economy. Meanwhile this attitude towards the kind of knowledge seams to be false. There are two points which justify this opinion. First of them concerns the relation between legal and ethical perspectives useful to evaluate business phenomena. Both axiological systems (in indicated background) are complementary to one another. It tends to the second argument. The relation between low and ethics makes necessary to indicate the public sphere as the place, where managers together with citizens and politicians – day by day – take part in debate about rules of social and economic correctness each of them.